Ichtyophagoi, their culture and economy: Survey and excavation in wadi bani khalid (WBK1, aqr zaida al athri) and tiwi - Loreto, Romolo (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
Project’s activities in the Sultanate of Oman, Ash-Sharqiyah North region, are directed towards the study of the Iron Age in northern Oman, in order to investigate those historical cultures known as fish-eating communities (Ichtyophagoi) from Greco-Roman sources and locally defined as Early to Late Iron Age cultural facies. From 2014 to 2018 the project focused on the study of the seasonal coastal economy of northern Oman in the Iron Age, in particular the phases of the 1st millennium BCE, between Qurayat and Ras Al Hadd, including Bamah and Tiwi as main coastal sites. Since 2018, the joint project has extended the area of research to urban oases further inland, along the Al Hajar mountain range, to define the settlement strategies between the Iron Age and the advent of Islam. These seasonal villages were in fact part of a complex socio-economic network involving the urban and agricultural oases in the interior, located along the Al Hajar mountain range, possessing their own hunting/fishing, farming and livestock economies, acted as bridges for trade between the coasts and the more inland regions, between Oman and the Emirates for at least the entire first half of the 1st millennium BCE and from the 1st century BCE to the 4th century CE.
Keywords: Archéologie -- Oman

The Medieval Town and Port of Damā (As Sib) on the Southern al-Bāținah Plain, Oman: Archaeological Fieldwork of the Italian-German-Omani Project in 2013 - Loreto, Romolo; Hoffmann, Göesta; Berardino, Simona; Priestman, Seth; Gajewska, Maria; Kennet, Derek; al-Motrāshi, Isma'il (Journal of Oman Studies, 2024)
In May 2013 Gõesta Hoffmann and Maurizio Tosi had the opportunity to document some surface clusters of Islamic period remains in the wilayät Sib, along the coastal area between Wadi Al Lawami and Wadi Al Khars. This consisted mainly of pottery dated between the early to late Islamic period (8th to 20th centuries CE). In June 2013, on behalf of the then Ministry of Ileritage and Culture, a first survey allowed us to recognise more archaeological materials focused around al-Rawdah Roundabout and the remains of a fort made of mudbricks and heavily obliterated by vegetation further to the south. In light of written sources referring to the ancient settlement of Damă as located in the southern al-Bäținah plain probably identifiable as As Sib (Seeb), further field analyses were undetaken in September 2013 in order to define the geoarchacological landscape via systematic survey, investigative excavations, and the definition of the palco coastline pertaining to the fort. The results of the project support the hypothesis that the ancient town and harbour of Dama is indeed to be located in present day As Sib.
Keywords: Archéologie -- Oman